How to write science fiction & fantasy - Card, Orson Scott (Cincinnati, Ohio : Writer's Digest Books, 2001)
You've always dreamed of writing science fiction and fantasy -- tales that pull readers into extraordinary new worlds and fantastic conflicts. Best-selling author Orson Scott Card shows you how it's done, distilling years of writing experience and publishing success into concise, no-nonsense advice. You'll learn how to: wield story elements that "define" the science fiction and fantasy genres; build, populate and dramatize a credible, inviting world your readers will want to explore; develop the "rules" of time, space and magic that affect your world and its inhabitants; construct a compelling story by developing ideas, characters and events that keep readers turning pages; find the markets for speculative fiction, reach them and get published; submit queries, write cover letters, find an agent and live the life of a writer. The boundaries of your imagination are infinite. Explore them with Orson Scott Card and create fiction that casts a spell over agents, publishers and readers from every world
Infinite boundary -- World creation -- Writing well -- Life and business of writing -- Index
Includes bibliographical references and index
cat
Hugo Award (Best non-fiction book), 1991
Keywords: Science fiction -- Authorship; Science fiction -- Technique; Fantasy literature -- Authorship; Fantasy literature -- Technique; Creative writing